Becoming Indian : The Struggle over Cherokee Identity in the Twenty-first Century - Sturm, Circe, 1967- (Book collections on Project MUSE., 2011)
" ... Racial shifter ... are people who have changed their racial self-identification from non-Indian to Indian on the U.S. census. Many racial shifters are people who, while looking for their roots, have recently discovered their Native American ancestry ..."